The Role of Father's Involvement and Social Competencies on Academic Achievement in Children - Risnawati, Erna; Rahmanadia, Hyunisa; Rahmawati, Orizka Desmi; Gusti, Valeria Yekti Kwasaning (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
This study aims to determine the relationship between father involvement and social competence on academic achievement in children. This study uses a correlational quantitative approach. The subjects in this study were fathers, teachers and children aged 8-13 years. The sampling technique in the study was accidental sampling. The number of samples in this study were 123 respondents. Measurements in this study used the Social Skills Improvement System (SSIS) scale from Gresham and Elliott, the Inventory of Father Involvement (IFI) scale from Hawkins and students' academic report cards. The data analysis technique used the Spearman correlation test. The results of this study indicate that there is no significant relationship between the role of father involvement and academic achievement but there is a significant relationship between social competence and academic achievement. This research is expected to have an impact on teachers, parents and schools to improve students' social competence to support students' academic